Correlation between Reduced FEF25-75% and a Positive Methacholine Challenge Test in Adults with Nonobstructive Baseline Spirometry - Irfan Shafiq; Mateen Haider Uzbeck; Zaid Zoumot; Mohamed Abuzakouk; Niyas Parappurath; Ali Saeed Wahla (Pulmonary Medicine)
Rationale. FEF25-75% is routinely reported on spirometry and is thought to be a marker of small airway obstruction. It is reduced in children with asthma, but its significance in adults and especially those without asthma diagnosis remains unclear. Objective. To clarify whether in adults with a nonobstructive spirometry a reduced FEF25-75% is associated with a positive methacholine challenge test (MCT). Methods. Data was collected for all the patients who had a MCT done between April 2014 and January 2020 but had nonobstructive baseline spirometry. Logistic regression was utilized to estimate the log odds of a positive methacholine test as a function of FEF25-75% and also for age, gender, BMI, FEV1, and FEV1/FVC. Results. Out of 496 patients, 187 (38%) had a positive MCT. Baseline characteristics in two groups were similar except that patients with positive MCT were younger (32±11.57 vs. 38±13.25 years, respectively, p<0.001). Mean FEF25-75% was lower in MCT positive (3.12±0.99 L/s) vs. MCT negative (3.39±0.97 L/s) patients, p=0.003. Logistic regression results suggest that MCT outcome is inversely related to FEF25-75%, age, and gender. Specifically, as FEF25-75% percentage of predicted value increases, the log odds of a positive MCT decrease (odds ratio OR=0.90, 95% confidence intervals CI=0.84‐0.96, p=0.002). Also, as age increases, the log odds of a positive MCT decrease (OR=0.95, 95%CI=0.94‐0.97, p<0.001). Conclusions. Reduced FEF25-75% in adults with nonobstructive spirometry can predict a positive response to MCT in younger patients. However, this relationship becomes weaker with increasing age.